2020
DOI: 10.1519/jsc.0000000000002882
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lower-Body Muscular Fatigue on Vertical Jump and Balance Performance

Abstract: Cooper, CN, Dabbs, NC, Davis, J, and Sauls, NM. Effects of lower-body muscular fatigue on vertical jump and balance performance. J Strength Cond Res 34(10): 2903–2910, 2020—Lower-body fatigue can lead to a decline in vertical jump (VJ) and balance performance due to decreased motor control and coordination. The purpose is to determine the effects of lower-body fatigue on VJ and balance performance. Twenty-four recreationally trained individuals participated in a single 1-hour familiarization and testing sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
6
22
1
2
Order By: Relevance
“…Fatigue index is calculated by the difference in PP from the minimum power all divided by PP. 14,15 Minimum power was calculated in order to determine the fatigue index. These indicators were not used in any statistical analyses due to the insignificant correlation with the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue index is calculated by the difference in PP from the minimum power all divided by PP. 14,15 Minimum power was calculated in order to determine the fatigue index. These indicators were not used in any statistical analyses due to the insignificant correlation with the study.…”
Section: Discussionmentioning
confidence: 99%
“…3,[10][11][12] Fatigue can be defined as a decline in muscular ability to maintain necessary mechanical work for a given function. 13 Fatigue has also been shown to have many effects on athletic performance, including a decrease in muscle control and strength 13 , decrease in ability to generate power 14 impaired strength, biomechanics, and central activation 12 . More specifically, several studies have shown that implementing a fatiguing protocol has shown a significant decrease in participants'…”
Section: Introductionmentioning
confidence: 99%
“…If a decrease in balance is detected, a training program may be recommended to improve athletes' balance and reduce the risk of injury (Knight et al, 2016). A well-designed resistance training program is a vital component to improve lower-body strength and it is important to apply exhaustive exercises to lower extremities on certain days (Cooper, Dabbs, Davis, & Sauls, 2018). Multiple exercises including dynamic/static, proactive and reactive types of balance should be used during balance training to target each balance dimensionindividually (Kiss, Schedler, & Muehlbauer, 2018)…”
Section: Study Limitations and Implications For Future Assessmentmentioning
confidence: 99%
“…Within basketball, standardized and repeatable jumping assessments are amongst the most popular to assess neuromuscular function [8][9][10][11][12]. The ability to produce substantial amounts of force onto the ground to vertically displace the center of mass is an important skill contextually within the game, since basketball athletes execute around 45 jumps per game [3].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this issue, repeated jumping and hopping tasks can be used, as they permit evaluating the ability to produce high vertical ground reaction forces in short ground contact times. In fact, the reactive strength index (RSI) (i.e., ratio of JH/contact time) has been previously used to measure both performance and fatigue within athletes [8,22].…”
Section: Introductionmentioning
confidence: 99%